A learning-based measurement framework for traffic matrix inference in software defined networks. (February 2018) - Malboubi, Mehdi; Peng, Shu-Ming; Sharma, Puneet; Chuah, Chen-Nee
Highlights: A framework for estimating flow sizes in software defined networks is proposed. An optimization formulation for providing optimal flow aggregates is proposed. An algorithm for measuring the most informative flows is presented. Graphical abstract: ISTAMP: an intelligent framework for measuring and inferring network flow sizes in software defined networks. Abstract: In this paper, we propose an intelligent framework for Traffic Matrix (TM) inference in Software Defined Networks (SDN) where the Ternary Content Addressable Memory (TCAM) entries of switches are partitioned into two parts to: 1) effectively aggregate part of incoming flows for aggregate measurements, and 2) de-aggregate and directly measure the most informative flows for per-flow measurements. These measurements are then processed to effectively estimate the size of network flows. Under hard resource constraints of limited TCAM sizes, we show how to design the optimal and efficient-compressed flow aggregation matrices. We propose an optimal Multi-Armed Bandit (MAB) based algorithm to adaptively measure the most rewarding flows. We evaluate the performance of our framework using real traffic traces from different network environments and by considering two main applications: TM estimation and Heavy Hitter (HH) detection. Moreover, we have implemented a prototype of our framework in Mininet to demonstrate its effectiveness.